The last days of Kira Mullan : a novel [large type] - French, Nicci (William Morrow Large Print, an imprint of HarperCollinsPublishers, 2025)
"Recovering from a psychotic breakdown, Nancy North moves into a new flat and becomes convinced a new neighbor's sudden death isn't a suicide, while Detective Maud O'Connor battles institutional apathy to uncover the truth, as both women face mounting pressure and blurred lines between reality and suspicion"--